Clínica Médica del hospital "Dos de Mayo" - Gonzáles Olaechea, Maximiliano (1922)
Inaugural lecture of the course of 1922. Medical Clinic "Dos de Mayo" hospital. by Dr. Maximiliano Gonzales Olaechea, Professor of Clinical Medicine at the Faculty of Medicine of the National Academy of Medicine of Lima.